Parkinson's in the bone - Lei Xiong; Jin-Xiu Pan; Hao-han Guo; Lin Mei; Wen-Cheng Xiong (Cell & Bioscience, 2021)
Abstract Patients with Parkinson’s disease (PD) exhibit systemic deficits, including arthritis and osteoporosis-like symptoms. However, the questions, how the deficits in periphery organs or tissues occur in PD patients, and what are the relationship (s) of the periphery tissue deficits with the brain pathology (e.g., dopamine neuron loss), are at the beginning stage to be investigated. Notice that both PD and osteoporosis are the products of a complex interaction of genetic and environmental risk factors. Genetic mutations in numerous genes have been identified in patients either with recessive or autosomal dominant PD. Most of these PD risk genes are ubiquitously expressed; and many of them are involved in regulation of bone metabolism. Here, we review the functions of the PD risk genes in regulating bone remodeling and homeostasis. The knowledge gaps in our understanding of the bone-to-brain axis in PD development are also outlined.